Method development and validation of Canagliflozin in human plasma by liquid chromatography tandem mass spectrometry (LC-MS/MS) - S. UDHAYAVANI; V. GIRIJA SASTRY; R. GOVINDA RAJAN; J. K. D. TEJASWI; R. RAJANI (International Journal of Pharma and Bio Sciences, 2018)
A rapid and sensitive bioanalytical method based on LC-MS with positive ion mode was developed for the determination of Canagliflozin in human plasma using Canagliflozin D4 as internal standard by using Solid Phase Extraction method. All validation parameters were performed and results were within the acceptance range for Bioanalytical assay as per USFDA Guidelines. The bioanalytical method described above is valid for the estimation of Canagliflozin, in human plasma over a range of 10.253 ng/mL to 6019.311 ng/mL. The total run time was 2.50 minutes at flow rate of 1.000 mL/minute. The Retention time of Canagliflozin and Canagliflozin D4 was found to be 1.5 ± 0.5 minutes and 1.5 ± 0.5 minutes. The recovery was found to be 98.07%. The method shows high extraction efficiency, low limit of quantitation and wide linear dynamic range which makes this a suitable method for use in clinical samples from Bioequivalence studies when compared with existing methods.